2016
DOI: 10.1155/2016/8582041
|View full text |Cite
|
Sign up to set email alerts
|

Impact of DEM Resolution and Spatial Scale: Analysis of Influence Factors and Parameters on Physically Based Distributed Model

Abstract: Physically based distributed hydrological models were used to describe small-scale hydrological information in detail. However, the sensitivity of the model to spatially varied parameters and inputs limits the accuracy for application. In this paper, relevant influence factors and sensitive parameters were analyzed to solve this problem. First, a set of digital elevation model (DEM) resolutions and channel thresholds were generated to extract the hydrological influence factors. Second, a numerical relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…), and output the results (discharge, water depth, and sediment transport) with user‐defined multiple spatial–temporal resolutions (Molnar & Julien, ). Previous studies on the predictive capacity of the CASC2D‐SED model suggested that this model is particularly useful for hydrological simulation in medium and small watersheds (usually less than 3,000 km 2 ) (Molnar & Julien, ; Zhang, Li, Saifullah, Li, & Li, ).…”
Section: Introductionmentioning
confidence: 99%
“…), and output the results (discharge, water depth, and sediment transport) with user‐defined multiple spatial–temporal resolutions (Molnar & Julien, ). Previous studies on the predictive capacity of the CASC2D‐SED model suggested that this model is particularly useful for hydrological simulation in medium and small watersheds (usually less than 3,000 km 2 ) (Molnar & Julien, ; Zhang, Li, Saifullah, Li, & Li, ).…”
Section: Introductionmentioning
confidence: 99%
“…The analyzed parameters/processes as well as the variations imposed on model inputs were defined based on previous calibrations of the MOHID-Land model for different watersheds [22,[25][26][27]. Additionally, the calibration processes performed on similar physically based models were also considered [49][50][51][52][53][54]. Thus, sixteen parameters/processes influencing water dynamics at the catchment scale were analyzed:…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…These authors found no statistically significant differences in the accuracy of DTMs varying between 10 and 2 m resolution when simulating streamflow and sediment yield using the WEPP model in a considerably smaller basin than the Ulla River catchment (the Centonara catchment in northern Italy, 1.92 km 2 ). Also, Zhang et al [51] and Nazari-Sharabian et al [53] showed the influence of the DTM resolution on the calibration of streamflow simulations using different physically based models.…”
Section: Impact Of Model Parameters/processes On River Flowmentioning
confidence: 99%
“…The parameters, such as soil, vegetation, precipitation, and underlying surface conditions are greatly influenced by DEM resolution. Zhang (2016) revealed DEM resolution plays an important role in the simulation process where higher DEM resolution results in the more accurate representation of terrain features. This is due to topography, which causes significant variations in solar irradiation over short distances.…”
Section: Role Dem Resolution To Improve the Accuracymentioning
confidence: 99%